Inovasi Sistem Administrasi Menuju Desa Digital dan Penyuluhan Tentang Pencegahan Stunting di Desa Ruhing Raya - Irwan, Andi Ilmi Utami; Kelana, Rustam; Marbun, Kurniawan Chandra; Febrianto, Teguh; Rita, Rita; Norde, Norde; Tanggara, Willyam Fernando Yuel (Fakultas Teknik Universitas Palangka Raya, 2024)
KKN is a mandatory program for students at the higher education level that aims to prepare students as successors of national development who are able to solve problems in society. KKN can help community development through various activities, including digital transformation and stunting prevention. Based on the results of KKN in Ruhing Raya Village, Gunung Bintang Awai District, South Barito Regency, Central Kalimantan Province, it can be concluded that KKN has had a positive impact on digital transformation and stunting prevention in Ruhing Raya Village. To improve the effectiveness of digital transformation, it is necessary to conduct socialization and training on the use of DigiDes to village officials and the community. In addition, village officials need to be more committed to using DigiDes. To improve the effectiveness of stunting prevention, it is necessary to conduct regular monitoring and evaluation of the programs that have been implemented. In addition, closer cooperation between the village government, health center, and the community needs to be improved.